Corporate Governance and Financial Performance: Empirical Evidence with Firm Size as a Moderating Variable - Nyoman Dewi Ayu Ratih Arya Dewanti; Made Sudarma; Mirna Amirya (ARRUS Journal of Social Sciences and Humanities, 2026)
This study aims to analyze the effect of Good Corporate Governance (GCG) mechanisms, represented by the board of commissioners, board of directors, and audit committee, on financial performance, as well as to examine the role of company size as a moderating variable. This is a quantitative study using secondary data from transportation and logistics companies listed on the Indonesia Stock Exchange for the period 2019-2024. The study population consisted of 38 companies, with a sample of 138 observations determined using purposive sampling techniques. Data analysis was performed using multiple linear regression and MRA. The results show that the board of directors has a positive and significant influence on financial performance. Meanwhile, the board of commissioners and audit committee have no direct influence. The moderation test shows that company size can strengthen the influence of the board of commissioners and audit committee on financial performance, but does not moderate the relationship between the board of directors and financial performance.